Development and characterization of channel catfish (Ictalurus punctatus) fermented salami-type inlaid including inulin as fat replacer - CAVENAGHI-ALTEMIO, Angela Dulce; MENEZES, Joice Cristina Catache; YOSHIHARA, Walkiria Tamiko; FONSECA, Gustavo Graciano (Food Science and Technology, 2024)
The aim of this study was to focus on developing formulations of fermented salami-type inlaid using channel catfish (Ictalurus punctatus) fillets as the main raw material and inulin as a fat replacer. Chemical, physical, microbiological, and sensory analyses were conducted to characterize the products. pH variation during maturation ranged from 5.53 to 4.76, with subsequent stabilization. Treatments showed a significant reduction in water activity from 0.90 to values below the required maximum for Italian-type salami. Shear force increased throughout maturation, with the 0.5% inulin treatment exhibiting lower values. Proximate composition analysis revealed high protein content (49.70–53.22%) and reduced lipid levels (5.32–5.75%). Sensory evaluation indicated overall acceptance above 70%, with purchase intention highest for sausages without inulin. This study underscores the potential of utilizing catfish fillets and inulin as fat substitutes in value-added meat products, offering improved nutritional profiles while maintaining sensory attributes.